2022
DOI: 10.1101/2022.08.18.22278875
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Short-term intensive fasting improves red blood cell function and rejuvenates erythropoiesis via regulating MS4A3-CDK2 module

Abstract: Fasting is known to improve health, but the precisely beneficial effects of specific types of fasting and their underlying mechanisms are not fully understood. We herein report that in humans, occasional short-term intensive fasting (STIF), a traditional fasting format favored by Asians, promotes erythropoiesis and boosts the function of red blood cells (RBCs) in oxygen transportation, ATP generation, antioxidant capacity, and innate immune response. The rejuvenation of erythropoiesis is more pronounced in hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…A recent study on seven days of water-only fasting also reported an increase in RBC levels and hemoglobin. They also reported that the increase in RBC levels is independent of RBC apoptosis, suggesting an upregulation of hematopoietic systems [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on seven days of water-only fasting also reported an increase in RBC levels and hemoglobin. They also reported that the increase in RBC levels is independent of RBC apoptosis, suggesting an upregulation of hematopoietic systems [ 31 ].…”
Section: Discussionmentioning
confidence: 99%